Resilience of progeny of Swietenia macrophylla to the simulated attack of Hypsipyla grandella in nursery (Scientia Agropecuaria, 2025)
The resilience of seedlings from four open-pollinated families of Swietenia macrophylla to simulated attacks by Hypsipyla grandella was evaluated at the nursery stage to determine the possibility of early selection of individuals from the most resilient families and establish sustainable forest plantations in the Peruvian Amazon. Significant differences were detected among families for diameter (D), sprout length (SL), and basal sprout area (BA). The coefficient of determination for genotypic effects was moderate (range: 0.248 – 0.457) for H (plant height), D, SL, and BA, and low (< 0.15) for plant base height (HB), number of sprouts (NR), number of branches (NB), and number of leaves (NL). The genetic correlation for the traits H, D, SL, BA, NR, NB, and NL ranged from 0.228 to 0.996, indicating that an increase in one of these traits can result in an increase in the other. This is important because there is the possibility of early selection of families for the traits D, SL, and BA for the development of plantations with families resistant to attack. Therefore, the genetic and phenotypic variation observed in the families suggests the possibility of early selection as a promising strategy for genetic improvement programs, using a larger number of families than those used in the present study, since theoretically larger samples may contain greater genetic variation between and within families.